THE EFFECT OF MASSAGE ON REDUCING FATIGUE AFTER TRAINING IN ACEH PABSI WEIGHTLIFTERS - Zulheri Is (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
This study aims to investigate the effect of massage therapy on reducing fatigue in weightlifters at the Indonesian Weightlifting Association (PABSI) Aceh. Data was collected from 15 athletes through pretests and postes using fatigue assessment instruments. The results of the data analysis showed that the average score of the pretest was 67.33, while the postes increased to 97.00. In addition, the median value of the pretest is 65.00 which rises to 95.00 in postes. The normality test shows that the pretest and posttest data are normally distributed (p > 0.05). T-test analysis yielded a t-count of 8.378, exceeding the table's t (1.76131) by significant values of 0.000 < 0.05. Therefore, there is a significant difference between pretes and postes, supporting the acceptance of alternative hypotheses. These findings suggest that massage therapy has a significant positive impact on reducing fatigue in weightlifters. The implications of this research can be used as a basis for further development of athletic recovery methods and contribute to a practical understanding of the benefits of massage in the context of weightlifting.